Employee Performance in the Medan Tourism Office: The Impact of Motivation and Discipline - hamidah Armaini (Institute of Computer Science (IOCS), 2022)
This study aims to find out the influence of work motivation and discipline on the performance of employees in the Medan Tourism Office. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study significantly influenced the performance of employees by 47.5%, hypothesis test obtained t calculate > t table or (7,052 > 2,004). Work discipline significantly influenced employee performance by 30.3%, hypothesis test obtained t count > t table or (4,892 > 2,004). Motivation and discipline of work simultaneously have a significant effect on employee performance with regression equation Y = 10,258 + 0.428X1 + 0.332X2 and influence contribution of 53.7%, hypothesis test obtained F calculate > F table or (31,275 > 2,780).